2014
DOI: 10.1002/ijc.28721
|View full text |Cite
|
Sign up to set email alerts
|

TBX2 blocks myogenesis and promotes proliferation in rhabdomyosarcoma cells

Abstract: Rhabdomyosarcomas (RMS) are the most frequent soft tissue sarcomas in children that share many features of developing skeletal muscle. We have discovered that a T-box family member, TBX2, is highly up regulated in tumor cells of both major RMS subtypes. TBX2 is a repressor that is often over expressed in cancer cells and is thought to function in bypassing cell growth control, including repression of p14 and p21. The cell cycle regulator p21 is required for the terminal differentiation of skeletal muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 36 publications
6
44
0
Order By: Relevance
“…The following antibodies were used: HDAC5 (Cell Signaling Technology), HDAC4 (Cell Signaling Technology), and rabbit IgG (Santa Cruz Biotechnology) as a nonspecific control. Primers corresponding to the LMOD2 and CDKN1A promoters were as described previously (32 …”
Section: Methodsmentioning
confidence: 99%
“…The following antibodies were used: HDAC5 (Cell Signaling Technology), HDAC4 (Cell Signaling Technology), and rabbit IgG (Santa Cruz Biotechnology) as a nonspecific control. Primers corresponding to the LMOD2 and CDKN1A promoters were as described previously (32 …”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Zhu et al (35) identified that TBX2 was highly upregulated in tumor cells of the major RMS subtypes. The results of this study demonstrated that elevated expression of TBX2 contributes to the pathology of RMS cells.…”
Section: Tbx Genes Are Involved In Tumor Cell Immortality and Prolifementioning
confidence: 99%
“…The results of this study demonstrated that elevated expression of TBX2 contributes to the pathology of RMS cells. TBX2 inhibited the regulatory factors myogenic differentiation 1 and myogenin, leading to the promotion of proliferation (35). Furthermore, TBX2 recruited the histone deacetylase HDAC1 and inhibited p21, which led to increased proliferation and decreased differentiation-specific gene expression (35).…”
Section: Tbx Genes Are Involved In Tumor Cell Immortality and Prolifementioning
confidence: 99%
See 2 more Smart Citations